Tranformasi Kurikulum Berbasis Kecerdasan Buatan Sebagai Strategi Adaptasi Pendidikan Abad 21: Artificial Intelligence-Based Curriculum Transformation as a 21st Century Education Adaptation Strategy - Hafidz Yuliansyah; Nur Saidah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Artificial intelligence (AI) technology has become an important element in supporting educational transformation in the era of society 5.0. This research aims to identify AI-based curriculum adaptation strategies that are relevant to the educational needs of the 21st century. The method used is literature by analyzing various literature, implementation practices, and case studies related to AI in education. This research focuses on three main aspects: planning, implementation, and evaluation of an AI-based curriculum. The research results show that AI can help curriculum planning through in-depth data analysis to produce adaptive learning materials that suit student preferences. In implementation, AI supports personalized learning through the use of virtual tutors, chatbots, and recommendation systems that adapt to individual learning styles. AI-based evaluation enables real-time data analysis to discover strengths and weaknesses in the learning process, thereby improving the overall quality of teaching. This research concludes that an AI-based curriculum can create education that is more inclusive, adaptive, and relevant to future needs. However, successful implementation requires technological infrastructure support, adequate digital literacy, and ethical guidelines for using AI in education